2004
DOI: 10.1007/s00204-004-0566-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of resveratrol against 6-hydroxydopamine-induced impairment of renal p-aminohippurate transport

Abstract: In the present study, the effects of resveratrol on 6-hydroxydopamine (6-OHDA)-induced p-aminohippurate (PAH) transport impairment were investigated in vitro using rat renal cortical slices. Cisplatin and cephaloridine (CPH), known nephrotoxins, were used as positive controls. In one series of experiments, renal cortical slices were incubated in a cisplatin-containing medium or a cisplatin-free medium. In another series of experiments, renal cortical slices were incubated in a CPH-containing medium, in a CPH- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To achieve this goal, we performed a state‐of‐the‐art microsurgical procedure to selectively remove sympathetic innervation of mouse hindlimb muscles without interfering with central sympathetic nuclei function, cardiac sympathetic innervation, the sympatho‐adrenomedullary system, or motor axons innervating the skeletal muscle. In contrast to the classical model of muscle denervation, in which sectioning the sciatic nerve or any of its branches engages sympathetic, sensory, and motor axons, and unlike prolonged chemical procedures, such as systemic 6(OH)DA administration, which induce sympathetic denervation, our procedure selectively depletes hindlimbs supplied exclusively by L2‐L3 paravertebral sympathetic ganglia …”
Section: Discussionmentioning
confidence: 99%
“…To achieve this goal, we performed a state‐of‐the‐art microsurgical procedure to selectively remove sympathetic innervation of mouse hindlimb muscles without interfering with central sympathetic nuclei function, cardiac sympathetic innervation, the sympatho‐adrenomedullary system, or motor axons innervating the skeletal muscle. In contrast to the classical model of muscle denervation, in which sectioning the sciatic nerve or any of its branches engages sympathetic, sensory, and motor axons, and unlike prolonged chemical procedures, such as systemic 6(OH)DA administration, which induce sympathetic denervation, our procedure selectively depletes hindlimbs supplied exclusively by L2‐L3 paravertebral sympathetic ganglia …”
Section: Discussionmentioning
confidence: 99%
“…5,6) In addition, recent studies suggest that dietary antioxidants and some foods, such as black grapes and Brassica rapa, can attenuate cisplatin-induced nephrotoxicity and hepatotoxicity. 28,29) The present study was designed to estimate the protective potential of the licorice extract, including speciesspecific antioxidative flavonoids, against cisplatin-induced nephrotoxicity and hepatotoxicity and whether its use influences the therapeutic efficacy of cisplatin, as well as its antitumor activity in an animal model.…”
Section: Discussionmentioning
confidence: 99%
“…28) In addition, it has been proposed that some foods, such as black grape, which contains resveratrol can provide significant protection against cisplatin-induced nephrotoxicity. 29) Epidemiological studies have shown that brassica vegetables, including cabbages, kale, Brussels sprouts and broccoli can play protective roles against several cancers.…”
Section: Discussionmentioning
confidence: 99%